Mecanismo de ação da atividade antinociceptiva e anti-inflamatória da Persea americana - LIMA, Nathalia de Fátima Melo (2018)
Introduction: Persea americana Mill is a plant species traditionally used in traditional Brazilian medicine for the treatment of inflammatory and algic processes. Objectives: To evaluate the anti-inflammatory and antinociceptive effect of the hydroalcoholic extract of the leaves of Persea americana Mill (EHPa) on pain and inflammation models, as well as to investigate the possible mechanisms involved in the action of this species. Materials and Methods: To identify the existing compounds in EHPa, the HPLC was terminated. The activity of EHPa was evaluated using mus musculus mice (males, ± 45 days) in the paw edema test induced by carrageenan and dextran, for anti-inflammatory action; abdominal contortions induced by acetic acid, formalin and glutamate for antinociceptive action. For evaluation of the involvement of opioid receptors and participation of the L-arginine-NO pathway in antinociceptive action, previously treated with naloxone and L-NAME, respectively. For in vitro analysis, the COX- 1 and COX-2 inhibition test was used. Results: The HPLC identified compounds such as β-amirin, caffeic acid, coumaric acid, isoquercitrin, naringerin and canferol. Treatment with EHPa (250 and 500mg / kg) reduced carrageenaninduced paw edema by 40% and 70%, respectively; A similar result was obtained with the 500mg / kg EHPa in the induction of dextran edema (50% reduction), evidencing the anti-inflammatory power of the species. In the in vitro test, the EHPa inhibited the Cycloxigenases, presenting greater selectivity for COX-2, when compared to COX-1. EHPa (50, 250 and 500mg / kg) reduced nociception caused by acetic acid, as well as the second (inflammatory) phase of the formalin test, in the neurogenic phase of the formalin test, EHPa at doses of 250 and 500 mg / kg was able to reduce the reaction time of the animals in 51% and 71.1% respectively . In the glutamate test, EHPa (50, 250 and 500mg / kg) reversed the nociception caused by intraplantar glutamate injection in 61.2%, 71.7% and 86% respectively. Naloxone was not able to reverse the action of EHPa (500mg / kg) in the neurogenic phase of the formalin test. In contrast, naloxone was able to block the antinociceptive effect of EHPa in the inflammatory phase. L-NAME was not able to reverse central antinociceptive action of EHPa; In the inflammatory phase, L-NAME was able to further increase the peripheral antinociceptive action of EHPa in 49.3%. Conclusion: EHPa has significant anti-inflammatory and antinociceptive effects. The anti-inflammatory action of EHPa involves the participation of histamine and / or 5HT, in addition to the inhibition of cycloxigenases, having greater COX-2 selectivity. Opioid receptors are not involved in the central antinociceptive activity of EHPa, but the possible participation of NMDA receptors was evidenced. The peripheral antinociceptive action of EHPa seems to involve opioid receptors and NO modulation.